N2‐Plasma‐Assisted One‐Step Alignment and Patterning of Graphene Oxide on a SiO2/Si Substrate Via the Langmuir–Blodgett Technique. Issue 5 (18th February 2015) - Chauhan, Neha; Palaninathan, Vivekanandan; Raveendran, Sreejith; Poulose, Aby Cheruvathoor; Nakajima, Yoshikata; Hasumura, Takashi; Uchida, Takashi; Hanajiri, Tatsuro; Maekawa, Toru; Kumar, D. Sakthi
Abstract : Precise control of the placement and patterning of graphene on various substrates has tremendous impact in many fields, such as nanoscale electronics, multifunctional optoelectronic devices, and molecular sensing. A one‐step facile technique involving N2 ‐plasma promotes surface modification and enhances the surface wettability of the substrate. The technique is employed to create partially hydrophilic surfaces on SiO2 /Si substrate with the aid of various templates, enabling the selective deposition, alignment, and formation of patterns comprising monolayer graphene oxide (GO) sheets; it successfully uses the Langmuir–Blodgett (LB) deposition technique over a large area without the need of any sophisticated equipment. Various characterization techniques are carried out in order to understand the possible mechanism behind the pinning of the GO on the partially treated areas. It is a relatively easy and swift process that can reliably accomplish specific surface modification with high bonding strength between GO and the substrate. This technique allows the creation of patterns with controllable dimensions. For example, the thickness of the GO sheets can be controlled; this is particularly important in creating arrays and devices at wafer‐scale. Being simple yet effective and inexpensive, this technique holds tremendous potential that can be exploited for numerous applications in the field of bio‐nanoelectronics. Abstract : Various geometric patterns of graphene oxide (GO) sheets on a SiO2 /Si substrate are produced using an inexpensive and lithography‐free method involving nitrogen plasma and the Langmuir–Blodgett technique. A possible mechanism behind the pinning of GO on the substrate is determined, and the bonding strength analysis is used to enable high‐throughput fabrication. This method's ability to place GO sheets on specific areas of a substrate may help to bring graphene research to real‐world applications.